Valorization of agricultural waste biomass via solar-driven gasification in regions with high solar resources: the case of Mexico - Maytorena-Soria, Victor Manuel; Buentello-Montoya, David Antonio; Aldana, Hugo (Frontiers in Chemical Engineering, 2025)
Gasification is a technology that can produce high-value fuels and chemicals from waste biomass, with challenges mainly associated to energy required and scaling up. At the same time, solar-driven gasification can tackle the problems associated to the energy required by allothermal systems, but its feasibility requires not only technological maturation, but also a strategic location. This work analyses the potential of solar gasification in Mexico using thermodynamic simulations, based on the Gibb’s Free Energy method, and geographical and demographic information. Results indicate that states with large waste biomass production (e.g., Sinaloa and Veracruz) are better suited for solar gasification than states with a large direct normal irradiance (e.g., Sonora), particularly when based on the H2/CO ratio of the syngas. An index (Per capita Energy Self-sufficiency Index, PESI) was defined to establish a metric for the potential of different states for solar gasification, and it was found that several states (for example, Sinaloa with 480% and Sonora with 245%) can produce more energy from solar gasification than their per capita consumption.